Apelinergic System Affects Electrocardiographic Abnormalities Induced by Doxorubicin - Kasper Buczma; Hubert Borzuta; Katarzyna Kamińska; Dorota Sztechman; Katarzyna Matusik; Jan Pawlonka; Michał Kowara; Barbara Buchalska; Agnieszka Cudnoch-Jędrzejewska (Biomedicines)
Background/Objectives: Anthracyclines remain a pivotal element of numerous tumor management regimens; however, their utilization is associated with a range of adverse effects, the most significant of which is cardiotoxicity. Research is constantly being conducted to identify substances that could be incorporated into ongoing cancer chemotherapy to mitigate anthracycline-induced cardiotoxicity. Recently, the apelinergic system has received a lot of attention in this field due to its involvement in cardiovascular regulation. Therefore, the aim of our study was to investigate the ability of the apelinergic system to inhibit the cardiotoxic effects of anthracycline—doxorubicin (DOX). Methods: In this study, 54 Sprague–Dawley rats were divided into seven groups and received intraperitoneal injections with DOX once a week for 4 consecutive weeks. The osmotic pumps provided a continuous release of NaCl (control groups), apelin-13 and elabela at two different doses, and the apelin receptor (APJ) antagonist ML221. Electrocardiography (ECG) and transthoracic echocardiography (TTE) with assessment of left ventricular (LV) systolic parameters were conducted on the first and last days of the experiment. Results: Lower doses of APJ agonists prevented the prolongation of QT and QTc intervals induced by DOX, while higher doses of these drugs exerted no such effect. The TTE examination confirmed DOX-induced LV systolic dysfunction. Moreover, the TTE examination revealed an improvement in the LV systolic parameters in the DOX-treated groups that were simultaneously administered APJ agonists. Conclusions: Our findings support the use of apelin and elabela as potential cardioprotective agents against anthracycline-induced cardiotoxicity.